Perception of Female Islamiyah School Students on Sokoto Caliphate Literature: Insights from Gwadabawa, Sokoto, Nigeria - Tambari Abbas Bashar (Al-Amīr Research Journal for Islamic Studies, 2024)
This study examines the perception and awareness of Sokoto Caliphate literature among female students in Islamiyah schools, focusing on Gwadabawa Local Government, Sokoto, Nigeria. The research aims to assess the students’ knowledge of Sokoto Caliphate literature and its historical contributions, particularly the works of Shehu Usmanu Danfodiyo. The findings indicate a low level of awareness, with only 13.8% of respondents able to articulate Shehu’s contributions to Islam in Hausaland. However, 93.75% of the participants expressed a strong interest in learning more about this intellectual heritage. These results underscore the need for strategic educational interventions to enhance the dissemination and integration of Sokoto Caliphate literature within the curriculum of Islamiyah schools, particularly for female students. This study contributes to the discourse on Islamic education and historical literacy, emphasizing the role of structured learning initiatives in preserving and promoting indigenous Islamic scholarship. Keywords: Islamiyah schools, Sokoto Caliphate, Shehu Usmanu Danfodiyo, Islamic education, historical awareness.